Clinicopathological significance of CADM4 expression, and its correlation with expression of E-cadherin and Ki-67 in colorectal adenocarcinomas. Issue 10 (20th June 2012) - Jang, Se Min; Han, Hulin; Jun, Young Jin; Jang, Si-Hyong; Min, Kyueng-Whan; Sim, Jongmin; Ahn, Hye In; Lee, Kang Hong; Jang, Ki-Seok; Paik, Seung Sam
Abstract : Aims: Cell adhesion molecule 4 (CADM4) is a novel tumour suppressor. The purpose of this study was to investigate the correlation between its expression and the expression of E-cadherin and Ki-67 in colorectal adenocarcinomas, as well as its effect on patient survival. Methods: We evaluated CADM4 expression in tissue microarrays of 513 colorectal adenocarcinomas by immunohistochemistry. Results: CADM4 was highly expressed in 210 of the 513 colorectal adenocarcinomas; expression was reduced in 185 cases and absent in the remaining cases. Loss of CADM4 expression was correlated with larger tumour size (6.2±2.1 cm vs 5.3±2.0 cm, p<0.001), mucinous tumour type (61.5% vs 20.9%, p<0.001), lymph node metastasis (31.4% vs 20.9%, p=0.022), higher Dukes stage (25.5% vs 19.6%, p=0.044), poorer differentiation (38.5% vs 18.8%, p<0.001), absence of E-cadherin expression (28.5% vs 16.0%, p=0.007) and presence of Ki-67 expression (27.3% vs 12.3%, p<0.001). In univariable Cox regression analysis, absence of CADM4 expression was associated with poorer overall survival (HR 0.712; 95% CI 0.512 to 0.989, p=0.042) and disease-free survival (HR 0.732; 95% CI 0.546 to 0.981, p=0.037). In multivariate analysis with the Cox proportional hazards model, CADM4 expression was not an independent prognostic factor of overall survival (HR 0.726; 95% CI 0.516 to 1.021, p=0.066) and disease-free survival (HR 0.762; 95% CI 0.563 to 1.033, p=0.080). Conclusions: Loss of CADM4 expression is relatively frequent in colorectal adenocarcinomas and may play an important role in cancer progression and patient survival.